Hidden and Lesser-known Disordered Eating Behaviors in Medical and Psychiatric Conditions - Manzato, Emilia; Cuzzolaro, Massimo; Donini, Lorenzo Maria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides up-to-date information on lesser known eating disorders (EDs) and eating related disorders. EDs and eating-related disorders include a highly heterogeneous group of syndromes and symptoms characterized by abnormal eating and weight control behaviors that can appear in all genders and ages. EDs can lead to high rates of morbidity and mortality, especially if they are misdiagnosed and untreated. The risk of underestimation is high for the lesser-known EDs, and when unhealthy eating behaviors appear in unusual situations, such as some medical and psychiatric pathologies, adults and the elderly, sexual minorities etc. The volume examines EDs in specific populations (the elderly, males, infants and toddlers, sexual minorities, etc.). Several chapters explore in detail lesser-known EDs (anorexia athletica, avoidant/restrictive food intake disorder, chewing and spitting, EDs by proxy, EDs after bariatric surgery, muscle dysmorphia, night-eating syndrome, nocturnal sleep-related eating disorder, orthorexia nervosa, pica, rumination disorder, etc.). Finally, other chapters address features of unhealthy eating and weight control behaviors associated with medical diseases (achalasia, craniopharyngioma, cystic fibrosis, cyclic vomiting syndrome, diabetes, dysphagia, Kleine-Levin syndrome, Klinefelter syndrome, Parkinson disease, Prader-Willi syndrome, Turner syndrome, etc.) The book will be a valuable resource for all health professionals who work in the fields of psychiatry, clinical psychology, eating disorders, obesity, medicine, clinical nutrition, public health, and prevention, allowing them to broaden their understanding of these disorders, and to enhance their clinical ability to diagnose them.
Preface -- 1. Muscle dysmorphia and disordered eating behavior -- 2. Eating disorders in infants and toddlersEating disorders in infants and toddlers -- 3. Eating disorders in males -- 4. Eating disorders in midlife and in the elderly -- 5. Eating and weight disorders in sexual and gender minorities -- 6. Food and Addictions -- 7. Post-traumatic eating disorders -- 8. Psychotropic drug induced disordered eating behaviors -- 9. Disordered eating behaviors in other psychiatric disorders -- 10. Avoidant/Restrictive Food Intake Disorder (Arfid) In Adults -- 11. Drunkorexia -- 12. Eating Disorders and bariatric surgery -- 13. Night-Eating Syndrome and Nocturnal Sleep-Related Eating Disorder -- 14. When healthy is taken too far. Orthorexia Nervosa: current state, controversies and future directions -- 15. Pica -- 16. Purging disorder -- 17. Rumination Disorder -- 18. Achalasia and disordered eating behaviors -- 19. Cancer and disordered eating behavior: the issue of anorexia -- 20. Celiac disease and eating and weight disorders -- 21. Craniopharyngioma and eating disorders -- 22. Cyclic vomiting syndrome -- 23. Current knowledge on eating experiences and behaviours in Cystic fibrosis: Exploring the challenges and potential opportunities for interventions -- 24. Diabetes type 2 and eating disorders -- 25. Type 1 Diabetes and Disordered Eating Behavior -- 26. Food allergies -- 27. Hirschsprung's Disease and Eating Disorders -- 28. Hypermobility spectrum disorders/Ehlers?Danlos syndrome and disordered eating behavior -- 29. Kleine-Levin syndrome and eating an weight disorders -- 30. Klinefelter syndrome and eating and weight disorders -- 31. Parkinson s disease and eating and weight disorders -- 32. Polycystic Ovary Syndrome and eating and weight disorders -- 33. Prader-Willi syndrome and eating and weight disorder -- 34. Turner syndrome and eating and weight disorders -- 35. Eating Behavior and Psychopathology in non-HIV lipodystrophic patients -- 36. Adipositas athletica, anorexia athletica,chewing and spitting, eating disorders by proxy, emetophobia, picky eating Symptoms, syndromes, or what? -- 37. CAIS Syndrome and eating and weight disorders.
Keywords: Psychiatry; Psychiatry; Feeding and Eating Disorders